2023
DOI: 10.3390/nano13040639
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Organic Methyl Orange (MO) Dye Using a Photocatalyzed Non-Ferrous Fenton Reaction

Abstract: Removal of recalcitrant organic pollutants by degradation or mineralization from industrial waste streams is continuously being explored to find viable options to apply on the commercial scale. Herein, we propose a titanium nanotube array (based on a non-ferrous Fenton system) for the successful degradation of a model contaminant azo dye, methyl orange, under simulated solar illumination. Titanium nanotube arrays were synthesized by anodizing a titanium film in an electrolyte medium containing water and ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The degradation products were characterized by electrospray quadrupole mass spectrometry (ESI Q MS), and the structural information on the possible intermediates in the degradation process have been listed in Table S3, and the mass spectra of some substances were shown in Figures S10–S15. The possible degradation pathway was speculated in conjunction with the literature, as shown in Figure . The mass spectral signal of MO corresponded to the deprotonated ion [M – H] − at m / z = 304, and all products were deprotonated ions [M – H] − obtained by ionization in the mass spectrum.…”
Section: Resultsmentioning
confidence: 96%
“…The degradation products were characterized by electrospray quadrupole mass spectrometry (ESI Q MS), and the structural information on the possible intermediates in the degradation process have been listed in Table S3, and the mass spectra of some substances were shown in Figures S10–S15. The possible degradation pathway was speculated in conjunction with the literature, as shown in Figure . The mass spectral signal of MO corresponded to the deprotonated ion [M – H] − at m / z = 304, and all products were deprotonated ions [M – H] − obtained by ionization in the mass spectrum.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies of methyl orange degradation employing total organic carbon (TOC) analysis demonstrate that decolorization is associated with loss of organic carbon, indicating the formation of inorganic products, which would be consistent with mineralization. 60,61 One recent study of methyl orange photodegradation by surface-modified Fe 3 O 4 nanoparticles in the presence of H 2 O 2 demonstrated that the colorless degradation products are significantly less toxic to fish than methyl orange. 62 Given the similarity of this photodegradation approach with the spinel ferrite photodegradation systems that are the subject of this Perspective, we strongly suspect that the colorless degradation products produced here are also primarily nontoxic mineralization products.…”
Section: Nonfunctionalized Pristine Surfaces Improve the Ability Of M...mentioning
confidence: 99%